Determinants of healthcare expenditure: Evidence from Switzerland between 1960-2022 - Thomas Brändle; Carsten Colombier; Benjamin Lerch (University of Basel, Center of Business and Economics (WWZ), 2025)
Healthcare expenditure growth is a key economic policy issue threatening the sustainability of public finances in advanced economies. This paper examines the determinants of healthcare expenditure in Switzerland using a time-series analysis for the period 1960-2022. Applying a dynamic OLS and an outlier-robust modified generalized maximum likelihood (MM) estimation approach, we find that income growth, population ageing, and Baumol's cost disease have all contributed to increasing total and public healthcare expenditure. The analysis suggests an income elasticity between 0.9 and 1.3, accounting for roughly half of the secular increase in healthcare expenditure. Our estimations also suggest a decrease in income elasticity over time. We find that population ageing has contributed by around 15% to the growth in healthcare expenditure. Income growth, demographic shifts, medical progress, slow productivity growth and labor shortages in healthcare are poised to intensify spending pressures in the years ahead, with implications both for total and public healthcare expenditure. Our results substantiate the policy debate on the determinants of healthcare expenditure, provide a tailored evidence basis for the healthcare expenditure projection framework for Switzerland and underscore the need for comprehensive reforms in the health sector to contain expenditure growth.
Keywords: H51; I18; J11; C22; 330; Health expenditure; public finances; income elasticity; population ageing; Baumol's cost disease